(untitled) (Journal of the College of Education for Women, 2019)
The world is currently standing on a huge ethical crossroad because of thescientific progress that produced many conclusions and removed the barricadesbetween humans , now it is extremely easy to reach everywhere thanks to thecommunications’ revolution , and now it is common to speak of things that wereprohibited until recently. This duality is clear in the meanings of words used indifferent languages spoken by the different nations of the world...Especially thosethat reflect the fundamentals of human existence like the words: ethics, conscience,culture and love, war and peace, interests, terrorism and others.One can also see the controversial relation between science and ethicsstarting from the truth that ethics have since emergence been connected to themind’s activity of differentiating between good and evil, and in the mind lies theability of scientific innovations…Through the ages, science and ethics walked sideby side each effecting the other, and the formation of society including the relationsthat are based on cooperation or competition, love or hatred and so on is the groundin which we exercise the building and evolution process which is based on thereconciliation of science and ethics.